ANALISIS PRODUK TOTAL KUE BANGKIT KHAS RIAU USAHA PENINGKATAN PENDAPATAN KELUARGA (UP2K) KEMBANG MELATI DI KOTA PEKANBARU - Annisa Mardatillah (UIR Press, 2016)
The research was conducted on Enterprise Income Families (UP2K) Jasmine Flower cake making thisrise is a company engaged in the field of small and medium industries, which aims at realizing the typicalwork of regional specialties Riau. Making cakes rise has worked or has received direct aid to thegovernment of industry ranging from the capital to the machine tool to process this produksi.Penelitianview of six indicators of Goods, Packaging, Brand, Label, service, and warranty. Analysing the totalproduct aims to defend the existence of the company, despite high levels of competition that exist today.With the increasing development of the times, the more stringent of competition that exist amongbusinesses. The purpose of research is to analyze the Total Product Jasmine Flower Cake Risen UP2K toincrease the number of customers and the quality of taste through the products manufactured. In thisstudy the authors use different types and sources of data are primary data and secondary data. Primarydata is data obtained directly from the object of study that includes data on the number of population, thequestionnaire data, interview data and other data deemed necessary. Secondary data is data obtaineddirectly from the company research. And using a second sampling technique is a technique for samplingcensus accidental sampling. The results of the six indicators is Good Enough, it shows that the cake isrisen Typical Processing Riau UP2K Jasmine Flower in Pekanbaru City must continue to increase thetotal product better future.